A new species of Neoseiulella (Acari: Phytoseiidae) from the Macaronesian Region, Canary Islands - Moraza, María L.; Peña Estévez, Miguel A. (Zootaxa, 2006)
A new species of mesostigmatid mite, Neoseiulella ferraguti sp. nov. collected from soil, litter and lichens of natural ecosystems on Tenerife island, Canary Islands is described. Neoseiulella ferraguti has two pairs of setae on the sternal shield, four pairs of preanal setae and two distinct pointed macrosetae on genu and basitarsus IV, macroseta on tibia IV slightly longer than other setae. A key for females of Neoseiulella species in the Canary Islands is provided.